Penggunaan Virtual Machine dalam Pembelajaran Jaringan - Budijono, Santoso; Saleh, Robby (Bina Nusantara University, 2014)
Computer Networks is an important course as a basis in computer science. This is because at this time all activities are associated with the use of network system or communication system. In the course of learning in Computer Networks, students are often difficult to understand network concepts, especially with many layman terms for students. The term IP, Subnet Mask, Gateway, and Router are the terms widely used in network. To better understand the use of the IP, Subnet Mask, Gateway, and Router, it should be given concrete examples of the application day-to-day. Such as setting the IP, Subnet, Gateway, and Router on a PC connected to the network, it is hoped that students can quickly understand. This prototype used some Virtual Machines considered to represent the need for the creation of multiple virtual machines in one computer. The resulting prototype is expected to be useful in learning the Networking matter in Computer Networks subject. Research successfully created 2 Virtual Machines in 1 computer, with the network in both Virtual Machines isolated and not connected to the Internet.